Adoption of Online Food Delivery By Culinary MSMEs in Bogor: Innovation Resistance Perspective - Aufa Hayya Qurrota A'yuni; Eko Ruddy Cahyadi; Megawati Simanjuntak (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: MSMEs are vital to Indonesia’s economy through job creation and poverty reduction, yet many remain hesitant to adopt digital technologies. Using Innovation Resistance Theory, this study investigates key functional and psychological barriers ranging from perceived value and usability to tradition and risk hindering OFD adoption. The findings aim to offer insights into overcoming these barriers and supporting the digital transformation of MSMEs.Purpose: This study explores the factors that influence the adoption of Online Food Delivery (OFD) platforms among MSMEs in Indonesia, focusing on both internal and external aspects. The internal factors while the external factors encompass environmental influences. Although geographically centered on Bogor City, the findings offer broader relevance, as the resistance patterns identified reflect systemic challenges faced by MSMEs nationwide. By employing the Innovation Resistance Theory, this study contributes to the design of inclusive digital strategies and supports Indonesia’s broader transition toward a sustainable, innovation-driven economy.Design/methodology/approach: This study employs a quantitative method utilizing linear regression to analyze the influence of various factors on the intention to use Online Food Delivery (OFD) services among Micro and Small Enterprises (MSEs) in Bogor, with a sample of 290 respondents selected through purposive sampling. The analysis results indicate that Competitive Pressure exhibits the highest path coefficient of 0.381, signifying that each unit increase in competitive pressure significantly enhances users' intention to adopt OFD, with a t-value reaching 7.632 (p < 0.01).Findings/Results: The SEM results reveal that competitive pressure (β = 0.38) and perceived trend (β = 0.19) positively influence OFD adoption, while usage barrier (β = -0.29) and value barrier (β = -0.30) are the strongest inhibitors. These findings contribute to the refinement of Innovation Resistance Theory in the context of MSME digital platform adoption.Conclusion: The successful adoption of Online Food Delivery (OFD) platforms among culinary MSEs in Bogor City requires overcoming functional and psychological barriers through targeted strategies that improve user experience and reduce perceived risks. This study not only offers practical insights to facilitate digital transformation and enterprise sustainability but also contributes theoretically by extending Innovation Resistance Theory within the context of digital platform adoption in developing economies.Originality/value: This study enhances the understanding of MSME adoption of OFD by examining internal and external resistance factors through Innovation Resistance Theory (IRT). It analyzes functional barriers (usage, value, risk), psychological barriers (tradition, image), and external factors (competitive pressure, perceived financial cost), providing a basis for future research on technology adoption across various sectors. Keywords: digital transformation, innovation resistance technology, micro and small enterprises, online food delivery, technology adoption